Evaluation of Polyphenol Content and Antioxidant Capacity of Fruits and Vegetables Using a Modified Enzymatic Extraction - Navarro-Lisboa, R; Lopez de Dicastillo-Bergamo, A (FACULTY FOOD TECHNOLOGY BIOTECHNOLOGY, 2016)
Fruits and vegetables are considered a good source of polyphenols and antioxidant capacities which are beneficial in protecting the human body against damage induced by reactive species. The objective of this work is to conduct an assessment of the polyphenol content and antioxidant activities of different fruit (kiwi, pear, green apple, raspberry, blackberry, strawberry and blueberry) and vegetable (pumpkin, green and red pepper) extracts using both chemical extraction and a modified in vitro digestive enzymatic extraction in order to compare results. Polyphenol content and antioxidant capacity of different fruits, vegetables and fruit juices were determined by Folin-Ciocalteu and FRAP methods, respectively. It was observed that polyphenol content expressed as gallic acid equivalents of extracts obtained with the two extraction methods was significantly (p<0.05) different (on average 310.3 and 231.8 mg per 100 g of fresh sample in enzymatic and methanolic extracts, respectively). Antioxidant capacity was also significantly (p<0.05) different in the extracts obtained by the two methods, with higher values in enzymatic extracts (1.91 mmol of Fe2+ per 100 g of fresh sample). Analyses of apple samples with and without skin also revealed important differences related to methodology and composition. Additionally, the original enzymatic extraction method was improved to avoid interferences caused by the presence of protein residues in the extract.